MATHEMATICS PROBLEM SOLVING BASED ON COGNITIVE STYLE TO DETERMINE OF STUDENT REASONING ABILITIES IN THE COVID-19 PANDEMIC ERA - Maswar Maswar; Mohammad Tohir; Diyah Ayu Rizki Pradita; Dian Noer Asyari; Wahyu Sardjono; Erna Selviyanti (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2022)
Mathematical problem solving has become an important issue that was often discussed in school classes including in the covid-19 pandemic era. This research aimed to describe the level of reasoning ability of students in solving mathematical problems based on the cognitive style of field-dependent and field-independent cognitive styles. The research approach used a was mixed-method of quantitative and qualitative. The subject of this study were students of Ibrahimy 1 Junior High School of Situbondo. The data collection techniques used were the form of tests and interviews. The data of the written test and interview results were tested for validity by triangulation. This research indicated that:(1) there were differences in student’s mathematical reasoning abilities between-FD and FI subjects; (2) the FI subject was able to re-examined, evaluated, and drew valid conclusions, but not for FD subject; (3) the FI subject has fulfilled all four mathematics reasoning indicators and classified as a very capable category; (4) the FD subject has fulfilled all three indicators and classified as capable enough category; and (5) generally, the level of mathematical reasoning ability of FI subjects group was very capable category as many as 21,43% and 14,29 % for FD subjects group.